Leading Change Together: Supporting Collaborative Practice through Joint Accreditation for Interprofessional Continuing Education. Issue 1 (31st December 2022) - Regnier, Kathleen; Travlos, Dimitra V.; Pace, Daniel; Powell, Sierra; Hunt, Allison
ABSTRACT: Interprofessional continuing education in support of team-based care is a critical component of healthcare quality and safety. In an effort to develop and advance the field of interprofessional continuing education (IPCE), the Accreditation Council for Continuing Medical Education (ACCME), the Accreditation Council for Pharmacy Education (ACPE), and the American Nurses Credentialing Center (ANCC) collaborated to launch Joint Accreditation for Interprofessional Continuing Education™, the first and only accrediting body in the world to offer the opportunity to be simultaneously accredited to provide CE activities for multiple healthcare professions through a single, unified application process, fee structure, and set of accreditation standards. To date, seven additional professions have joined Joint Accreditation: athletic trainers, dentists, dieticians, optometrists, physician associates/physician assistants (PAs), psychologists, and social workers. With this expansion, jointly accredited organisations can choose to offer IPCE for up to ten professions without needing to attain separate accreditations. Jointly accredited providers are able to offer education that is designed for single professions, multiple professions, and interprofessional teams, as long as 25% of the education is interprofessional. This innovation facilitates and incentivises IPCE which leads to improved healthcare delivery and better patient outcomes. To effectively integrate interprofessional collaborative practice throughout healthcare systems across the world, IPCE needs to become an integral part of lifelong learning for all health professions. There are several jointly accredited organisations that operate outside of the USA, and interest in Joint Accreditation and IPCE continues to grow.